Treatment patterns, resource utilization, and outcomes among hospitalized patients with methicillin-resistant Staphylococcus aureus complicated skin and soft tissue infections in Lebanon and Saudi Arabia - Matar MJ (Infection and Drug Resistance, 2017)
Madonna J Matar,1 Rima Moghnieh,2 Adel F Alothman,3 Abdulhakeem O Althaqafi,4 Thamer H Alenazi,3 Fayssal M Farahat,4 Shelby Corman,5 Caitlyn T Solem,5 Nirvana Raghubir,6 Cynthia Macahilig,7 Seema Haider,8 Jennifer M Stephens5 1Department of Infectious Diseases, Notre Dame des Secours University Hospital, Jbeil, Lebanon; 2Department of Internal Medicine, Makassed General Hospital, Beirut, Lebanon; 3College of Medicine, King Saud bin Abdulaziz University for Health Sciences, King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 4King Abdullah International Medical Research Center, Infection Prevention and Control, King AbdulAziz Medical City, King Saud bin AbdulAziz University for Health Sciences, Jeddah, Saudi Arabia; 5Pharmerit International, Real-World Evidence/Data Analytics, Bethesda, MD, 6Pfizer, New York, NY, 7Medical Data Analytics, Parsippany, NJ, 8Pfizer, Groton, CT, USA Objectives: To describe treatment patterns and medical resource use for methicillin-resistant Staphylococcus aureus (MRSA) complicated skin and soft tissue infections (cSSTI) in Saudi Arabia and Lebanon in terms of drug selection against the infecting pathogen as well as hospital resource utilization and clinical outcomes among patients with these infections. Methods: This retrospective chart review study evaluated 2011–2012 data from five hospitals in Saudi Arabia and Lebanon. Patients were included if they had been discharged with a diagnosis of MRSA cSSTI, which was culture-proven or suspected based on clinical criteria. Hospital data were abstracted for a random sample of patients with each infection type to capture demographics, treatment patterns, hospital resource utilization, and clinical outcomes. Statistical analysis was descriptive. Results: Data were abstracted from medical records of 87 patients with MRSA cSSTI; mean age 52.4±25.9 years and 61% male. Only 64% of patients received an MRSA active initial therapy, with 56% of first-line regimens containing older beta-lactams. The mean total length of stay was 26.3 days, with the majority (19.1 days) spent in general wards. Surgical procedures included incision and drainage (22% of patients), debridement (14%), and amputation (5%). Mechanical ventilation was required by 9% of patients, with a mean duration of 18 days per patient. Hemodialysis was required by four patients (5%), two of whom were reported to have moderate to severe renal disease on admission, for a mean of 5.5 days. Inpatient mortality was 8%. Thirty-nine percent were prescribed at least one antibiotic at discharge, with the most commonly prescribed discharge antibiotics being clindamycin (44%), ciprofloxacin (18%), trimethoprim/sulfamethoxazole (12%), and linezolid (9%). Conclusion: This Middle Eastern real-world study of resource use and treatment patterns in MRSA cSSTI indicates that management of this condition could be further optimized in terms of drug selection and resource utilization. Keywords: antibiotics, length of stay, Saudi Arabia, Lebanon, skin, skin structure infections